Olhares acerca do processo de construção dos projetos políticos pedagógicos dos cursos técnicos integrados ao Ensino Médio de jovens e adultos no contexto do Ifes Campus Vitória - Scopel, Edna Graça (2012)
This paper presents the findings of an investigation that aimed to analyze the process of construction of the Pedagogical Political Projects of Proeja’s courses in the context of Ifes campus Vitória. The research problem sought to capture movements and experiences triggered in this process. In the methodological approach, with an emphasis on qualitative research, it was necessary to entwine two approaches: school ethnography and action research due to the researcher's professional practice in the locus of the study. Various instruments were used to data survey and production, which include: questionnaires, interviews, a field diary of the observations, literature and documental research. Approximately 80 people participated in this study, including teachers, students and administrators, addressed in specific contexts: the group of continuing education, the committee of the projects, the students' meetings, intermediate pedagogical meeting, among others. The theoretical and methodological framework lined with the historical and dialectical materialism perspective founded the entire investigative trajectory, consistent with the basis of production of the research on labor and education and by constituting the reference that underlies the structuring principles of the integrated curriculum in the human perspective. Through the metaphor of observatories, we focus our lenses on the issues that challenged the construction of pedagogical and political projects, their consistency with Proeja’s epistemological, political and pedagogical principles. In this movement, various looks were captured, enabling us to raise the following results: the path of building the projects was marked by contradictions that pervade the whole process and that constituted a meaningful discussion that tensions the pedagogical, administrative and financial management of Ifes campus Vitória. The movement was also a process of building, sharing of knowledge and experiences, driven by the pursuit to learn the sense of integration that contradictorily did not achieve its goals, although one cannot deny the positive results of the process within the institution. Thus, the challenges for effective integrated formation at Ifes persist. The subjects to whom the program turns to and their demands and formation, as well as the material conditions of the courses offering and specially the conditions of the teachers' involvement with the program and the reflections about their practices earn centrality in this discussion.